생쥐의 난소 발달과정에서 Solute carrier family 유전자들의 발현양상 - 오이균; Lee-gyun O; 박창은; Chang-eun Park (Korean journal of clinical laboratory science, 2017)
난포 내 난자를 둘러싸고 있는 과립세포는 난자를 위한 성장상태 및 난포의 발달에 중요하다. Solute carrier family 유전자는 스테로이드 호르몬, 다양한 약물, 몇몇 다른 기질을 유입시킨다. 연구에서 획득한 서로 다르게 발현하는 유전자들 (DEGs) 중 일부를 in situ hybridization을 통해 분석하였다. 분석한 결과SLC23A3과 SLC39A10이 난소에서 높게 발현하였다. SLC39A10유전자는 원시난포에서 높게 발현하였고, SLC23A3은 일차, 이차 난포에서 높게 발현하였다. 특히 성장하는 난포의 과립막 세포에서 발현하였다. SLC23A3과 SLC39A10은 원시난포와 일차난포에서 다르게 발현하는 것은 각 난포의 분리를 통해 좀 더 확인해야 할 것이다. 본 연구에서는 유전자 발현 정보를 통해 원시난포의 개시와 성장을 위한 전환에 관여하는 기전을 이해하는데 기초정보와 난포발달 촉진을 위한 난소기능부전의 기전을 규명하는데 정보를 제공할 것으로 기대된다. Granulosa cells, which surround the oocyte within the ovarian follicle, play an essential role in creating conditions required for the development of oocytes and follicles. The solute carrier family (SLC) is comprised of influx transporters of steroidal hormones, various drugs, and several other substrates. The differential expression of selected DEGs was confirmed using in situ hybridization analysis. SLC23A3 and SLC39A10 were highly expressed in the ovary. The SLC39A10 gene was expressed in the primordial follicle stage, but SLC23A3 was expressed in the growing follicle stage. Contrastingly, the expression of SLC23A3 was increased in granulosa cells at the growing follicle stage. The differential expressions of SLC23A3 and SLC39A10 between the primordial and primary follicles were additionally confirmed by using follicle isolations. The gene expression profile from the present study may provide insight for future studies on the mechanism(s) involved in primordial-primary follicular transition and suggestions to promote follicular development in ovarian dysfunction.